Muscle differentiation in a colonial ascidian: organisation, gene expression and evolutionary considerations. - Degasperi, V; Gasparini, F; Shimeld, S; Sinigaglia, C; Burighel, P; Manni, L (2009)
BACKGROUND: Ascidians are tunicates, the taxon recently proposed as sister group to the vertebrates. They possess a chordate-like swimming larva, which metamorphoses into a sessile adult. Several ascidian species form colonies of clonal individuals by asexual reproduction. During their life cycle, ascidians present three muscle types: striated in larval tail, striated in the heart, and unstriated in the adult body-wall. RESULTS: In the colonial ascidian Botryllus schlosseri, we investigated organisation, differentiation and gene expression of muscle beginning from early buds to adults and during zooid regression. We characterised transcripts for troponin T (BsTnT-c), adult muscle-type (BsMA2) and cytoplasmic-type (BsCA1) actins, followed by in situ hybridisation (ISH) on sections to establish the spatio-temporal expression of BsTnT-c and BsMA2 during asexual reproduction and in the larva. Moreover, we characterised actin genomic sequences, which by comparison with other metazoans revealed conserved intron patterns. CONCLUSION: Integration of data from ISH, phalloidin staining and TEM allowed us to follow the phases of differentiation of the three muscle kinds, which differ in expression pattern of the two transcripts. Moreover, phylogenetic analyses provided evidence for the close relationship between tunicate and vertebrate muscle genes. The characteristics and plasticity of muscles in tunicates are discussed.